Measuring K0SK± interactions using Pb-Pb collisions at √sNN=2.76 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Klewin, Sebastian; Leardini, Lucia; Mercado Pérez, Jorge; Oeschler, Helmut; Ohlson, Alice; et al. (Physics letters, 2017)
We present the first ever measurements of femtoscopic correlations between the KS0 and K± particles. The analysis was performed on the data from Pb-Pb collisions at sNN=2.76 TeV measured by the ALICE experiment. The observed femtoscopic correlations are consistent with final-state interactions proceeding via the a0(980) resonance. The extracted kaon source radius and correlation strength parameters for KS0K− are found to be equal within the experimental uncertainties to those for KS0K+. Comparing the results of the present study with those from published identical-kaon femtoscopic studies by ALICE, mass and coupling parameters for the a0 resonance are tested. Our results are also compatible with the interpretation of the a0 having a tetraquark structure instead of that of a diquark.